Preliminary Reflection on Performance Indicator and Performance Factor for Infrastructure Asset Management - Hitapriya Suprayitno; Ria Asih Aryani Soemitro; Mahendra Andiek Maulana; Yervi Hesna (Journal of Infrastructure & Facility Asset Management, 2020)
Performance Evaluation is routine work for IAM. Related to this, the Performance Indicator and Performance Factor need to be well understood. This paper present the result of a preliminary reflection on infrastructure performance, performance indicator and performance factor. Basic Quality of infrastructure is measure by its Performance to execute its Function. Performance Factor is something that can influence the Performance. Performance may consists of several components. Each Performance components indicate different qualities. Each performance components may have different importance level and different value. Factor may consists of several factors. Each factor has its own nature as supporting or resisting to performance. Each factor has its own strength of influence, its own easiness to be manipulated, and its value.